Cherry stones as precursor of activated carbons for supercapacitors - Olivares-Marín, M.; Fernández, J. A.; Lázaro, M. J.; Fernández-González, C.; Macías-García, A.; Gómez-Serrano, V.; Stoeckli, Fritz; Centeno, Teresa A. (My University, 2009)
It is shown that cherry stones-wastes can be recycled as activated carbons for electrode material in supercapacitors. KOH-activation of this precursor at 800–900 °C is an efficient process to obtain carbons with large specific surface areas (1100–1300 m2 g−1), average pore sizes around 0.9–1.3 nm, which makes them accessible to electrolyte ions, and conductivities between 1 and 2 S cm−1. These features lead to capacitances at low current density as high as 230 F g−1 in 2 M H2SO4 aqueous electrolyte and 120 F g−1 in the aprotic medium 1 M (C2H5)4NBF4/acetonitrile. Furthermore, high performance is also achieved at high current densities, which means that this type of materials competes well with commercial carbons used at present in supercapacitors.
Keywords: microporous materials; surfaces; adsorption; electrochemical properties